2020
DOI: 10.1111/jan.14718
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of residents in the prevention and control of COVID‐19: An online questionnaire survey

Abstract: Aims To explore the status quo and the influencing factors of residents’ knowledge, attitude and practice (KAP) in the prevention and control of coronavirus disease 2019 (COVID‐19), and the difficulties or challenges perceived by residents in their preventive practice. Design An online questionnaire survey. Methods The self‐designed questionnaire was distributed among residents online in February 2020. Descriptive statistics, two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
37
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 30 publications
11
37
4
Order By: Relevance
“…These noted knowledge gaps arose primarily because medical and agricultural majors’ students might have had biological sciences knowledge which is linked to infectious and virus diseases prior to the pandemic, as it might also be in their curriculum of study and is related to their professions which would have positively given them an added advantage of having good knowledge. The general findings of good knowledge on COVID-19 of this study are in agreement with other results that were conducted on similar topics on COVID-19 in other countries like China, India, Bangladesh, Cameroon, Nigeria, and Turkey 6 , 21 , 22 , 31 , 32 , 36 , 37 recently. Furthermore, on knowledge gaps, the study is in conformity with results in other areas where pandemics like Cholera, Ebola, Avian Influenza (H5N1), N1H1 Flu Virus, and COVID-19 knowledge were researched like Thailand, Ecuador, Ethiopia, and Nigeria where they also found that there were knowledge gaps among people depending on social demographic factors like academic background, sex, and age.…”
Section: Discussionsupporting
confidence: 93%
“…These noted knowledge gaps arose primarily because medical and agricultural majors’ students might have had biological sciences knowledge which is linked to infectious and virus diseases prior to the pandemic, as it might also be in their curriculum of study and is related to their professions which would have positively given them an added advantage of having good knowledge. The general findings of good knowledge on COVID-19 of this study are in agreement with other results that were conducted on similar topics on COVID-19 in other countries like China, India, Bangladesh, Cameroon, Nigeria, and Turkey 6 , 21 , 22 , 31 , 32 , 36 , 37 recently. Furthermore, on knowledge gaps, the study is in conformity with results in other areas where pandemics like Cholera, Ebola, Avian Influenza (H5N1), N1H1 Flu Virus, and COVID-19 knowledge were researched like Thailand, Ecuador, Ethiopia, and Nigeria where they also found that there were knowledge gaps among people depending on social demographic factors like academic background, sex, and age.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that gender was a factor affecting practice. Females showed better protective practice, consistent with the results of a study in Vietnam (27), which may be related to the fact that males were more likely to engage in risk-taking behavior (28). Knowledge is the basis for establishing correct attitudes to change practice, while the attitude is the driving force of practice change.…”
Section: Discussionsupporting
confidence: 82%
“…As such, it was not surprising that the socioeconomic divide in prevalence observed in Phase I had mostly disappeared and even appeared reversed by Phase IV. Importantly, Phase IV was the first time the modal surveyed age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) also demonstrated model seropositivity (24.9%). This trend mimicked hospitalisation and test positivity records since December 2020 3 .…”
Section: Discussionmentioning
confidence: 99%
“…An adapted short questionnaire (see extended data 29 ) was administered to capture participant socio-demographic data, COVID-19 knowledge, attitudes and perceptions (KAP) 30,31 and COVID-19 testing history during the study. The draft questionnaire was field tested in July 2020 at Greater Accra Regional Hospital among healthcare workers.…”
Section: Data Management and Analysismentioning
confidence: 99%